If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y + 3 = 5y + 14 Reorder the terms: 3 + 13y = 5y + 14 Reorder the terms: 3 + 13y = 14 + 5y Solving 3 + 13y = 14 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 3 + 13y + -5y = 14 + 5y + -5y Combine like terms: 13y + -5y = 8y 3 + 8y = 14 + 5y + -5y Combine like terms: 5y + -5y = 0 3 + 8y = 14 + 0 3 + 8y = 14 Add '-3' to each side of the equation. 3 + -3 + 8y = 14 + -3 Combine like terms: 3 + -3 = 0 0 + 8y = 14 + -3 8y = 14 + -3 Combine like terms: 14 + -3 = 11 8y = 11 Divide each side by '8'. y = 1.375 Simplifying y = 1.375
| 6(a+2)+2c=b-a+27 | | 1.8x-40+32= | | y-2=5/3(x-5) | | 2x=4*4 | | 3y^2+9y+1=0 | | (2xy+y^4)dx+(3x^2+6xy^3)dy=o | | 0.11k+1.5=2 | | (28)^3/4 | | 8m=9+13+8m | | 3x^2+9x-12=6 | | X+12=2(x+1) | | 40/2*5 | | 6x+1=x+22 | | (112/100)^(3/4) | | 3x-9y=25 | | x/3*2=1 | | log(x)=.1x | | q=400/p | | (112/100)^3/4 | | 2y+10y=12 | | ln(x)=.1x | | 4(3x-4)-48=5x-2 | | 3+-3*6+2=5 | | 10=3x+6+x | | 12y+5=3y+12 | | -3(4x+1)=-12x+3 | | -x^2-18x-145=0 | | 82=12+10s | | -3+4y+2y=6+2y+2y | | (2x+4)(2x-4)=8 | | a+1.25=2.7 | | 22p+25p+15p+22p=1008 |